Electrical and rheological percolation behavior of multiwalled carbon nanotube-reinforced poly(phenylene sulfide) composites. (January 2017) - Ribeiro, B; Pipes, RB; Costa, ML; Botelho, EC
Polyphenylene sulfide-based nanocomposites filled with unmodified multiwalled carbon nanotubes from 0.5 wt% to 8.0 wt% have been prepared by melt mixing technique with a single-screw extruder and hot press. Transmission electronic microscopy and scanning electron microscopy analysis were carried out in order to assess the multiwalled carbon nanotubes dispersion throughout the polyphenylene sulfide matrix. Electrical conductivity of the polymer was dramatically enhanced by about 11 decades between 2.0 wt% and 3.0 wt% of nanotubes, suggesting the formation of three-dimensional conductive network within the polymeric matrix. The storage modulus (G′) of neat polyphenylene sulfide presented an increase by two orders of magnitude when 2.0 wt% of pristine multiwalled carbon nanotubes was considered, with the formation of an interconnected nanotube structure, indicative of "pseudo-solid-like" behavior. In addition, percolation networks were formed when the loading levels achieve up to 1.5 wt% for multiwalled carbon nanotubes/polyphenylene sulfide composites.